PEMBELAJARAN MATEMATIKA BERBASIS MATH EDUTAINMENT DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS BAGI PESERTA DIDIK KELAS V DI SDN CICALENGKA 08 - Andriani Nurcahya, Mila; Rakhmayanti, Fully (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Currently learning mathematics that is carried out in elementary schools still uses old or traditional methods. The lack of innovation in the implementation of learning mathematics makes students lose enthusiasm and interest in participating in the learning process. Through learning mathematics based on Math Edutainment, it can increase students' interest in learning mathematics, namely learning can be done while playing. This study aims to determine the application of Math Edutainment-based mathematics learning in improving the mathematical problem solving abilities of class V at SDN Cicalengka 08. The method used in this research is to use qualitative research methods through a descriptive approach. The results obtained from this study are that learning mathematics in Class V students at SDN Cicalengka 08 by using the application of Math Edutainment can improve understanding in learning mathematics. This, based on the application of learning while playing in the process of learning mathematics can also increase the attractiveness of students to take part in learning. Therefore, students' mathematical solving abilities can be further improved in the learning process.